Microsoft Visual C++ 2005 express edition programming for the absolute beginner - Miller, Aaron (Thomson/Course Technology, 2006)
Microsoft Visual C++ 2005 Express Edition Programming for the Absolute Beginner focuses on teaching first time programmers how to program using Visual C++ 2005 Express Edition as a foundation language. Written for the entry-level user, the book assumes no prior programming or scripting experience. Whether you are a new or experienced C++ developer, this book delivers the tools and libraries you need to write a variety of programs. Written in a straight-forward style, using a games-based approach that makes learning beginning-level programming fun and easy, Microsoft Visual C++ 2005 Express Edition Programming for the Absolute Beginner is the perfect introductory programming book.